Interdental distraction osteogenesis for the management of alveolar clefts: archwise distraction - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2012)
Bone grafting is a successful protocol for cleft repair but it is very challenging to close large gaps using local gingival tissue. In the last decade, interdental distraction osteogenesis has been introduced as a successful treatment protocol for repairing such large clefts. In this article a new method for closing the alveolar cleft is introduced and one case is presented. A tooth supported distractor which was specially designed to be inserted on to the main arch wire was used for the distraction. The aim was to distract the tooth segments through the curve of the dental arch and achieve complete closure of the gaps. The distractor introduced had several advantages: it is simple to apply, activate and remove; there is no need for a second operation; it is an outpatient procedure. In the case reported, a very large gap was successfully closed using this protocol whilst maintaining the ideal arch form and generating new bone behind the distracted segments.
Keywords: distraction osteogenesis; alveolar clefts; bone regeneration